Malawi : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2002)
This paper presents report on the Observance of Standards and Codes-Fiscal Transparency Module for Malawi. A number of improvements have been made to budget management in Malawi in recent years that are increasing the level of fiscal transparency. Notable examples include the development of a sophisticated budget classification system and the introduction of the Medium-Term Expenditure Framework (MTEF) budgeting process. However, the developments have not been applied consistently across the different areas of fiscal management, and there has been insufficient attention to data quality.